CANADA: THE EXPERIENCE OF ACHIEVING NATIONAL UNITY (Scientific journal of the Fergana State University, 2025)
In the 1970s, Canada began to implement a policy of multiculturalism with the aim of regulating interethnic relations. The status of this political model is enshrined in constitutional law. Multiculturalism contributed to the formation of a political and cultural consensus in Canada. At the same time, its implementation also gave rise to problematic situations. This article examines the history and evolution of the concept of multiculturalism in Canada.